PENGARUH PENGALAMAN AUDITOR DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI - Dessi Antika Putri (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2020)
This study aims to obtain empirical evidence of the influence of Audit Experience and Time budget pressure on Audit Quality with Auditor Ethics as Moderation Variables. The population in this study are auditors who work at public accounting firms in DKI Jakarta. Sampling use convenience sampling totaling 125 respondents. The primary data collection method used was a questionnaire method. Data were analyzed using multiple regression with moderation. The results showed that the Auditor's Experience had a positive effect on Audit Quality, while Time budget pressure had a negative effect on Audit Quality. This study also shows that the Auditor Ethics as a moderating strengthens the positive influence between the Auditor's Experience on Audit Quality, while the Auditor Ethics as a moderating weakens the negative influence of Time budget pressure on Audit Quality.